Kolaborasi Strategi Reading Aloud Dan Two Stay Two Stray sebagai Upaya Meningkatkan Minat dan Prestasi Belajar Siswa pada Mata Pelajaran Bahasa Inggris Kelas VII A SMP Negeri 3 Taliwang - Suhada (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2020)
The research objective was to increase student interest and achievement in English by using the collaborative reading aloud strategy and two stay two stray. This classroom action research uses subjects and data sources for class VII A SMP Negeri 3 Taliwang school year 2019/2020 in English with 29 students. Kemmis and Taggart's plot method research design with a cycle model. Research data collection uses observation techniques and learning outcomes tests. The data analysis procedure used interactive model analysis by Milles and Huberman. Based on the analysis of test results and findings in the reflection-evaluation of learning activities, it can be concluded that; 1) through appropriate procedures and steps, the collaborative use of reading aloud and two stay two stray strategies can increase student interest and learning achievement in English, 2) The application of this collaborative strategy increases student interest in learning. This can be seen from the increase in value in aspects of student activities who show interest in participating in learning, namely: a) reading aloud, b) listening to readings, c) focusing attention, d) cooperation, e) seeking answers, and f) presentation, 3 ) Student learning achievement in English with the application of collaborative reading aloud and two stay two stray strategies in learning tends to increase in each cycle. The percentage and number of students who scored above the KKM reached 75%, 4) Students' perceptions of the use of collaborative reading aloud and two stay two stray strategies applied in this study were very positive, students were very happy and very interested in this strategy was used in presenting the material and subjects other than English. This collaborative strategy is very effective in increasing student interest and learning achievement when learning is understood about the steps for using this strategy, the teacher guides students who have difficulty in the learning process, and at the end of the lesson, an evaluation test is given and reflects on learning activities